Comparison of subacromial ketorolac injection zversus corticosteroid injection in the treatment of shoulder impingement syndrome - Parisa Taheri; Farnaz Dehghan; Sahar Mousavi; Reza Solouki (Wolters Kluwer Medknow Publications, 2017)
Objective: Subacromial impingement syndrome is the most common cause of shoulder pain and restriction in range of motion in the world. The aim of this study was to compare the efficacy of subacromial injection of ketorolac with the injection of corticosteroid for the treatment of subacromial impingement syndrome. Methods: A total of forty patients were randomly allocated into two groups. Group A received 40 mg of methylprednisolone and Group B received 60 mg of ketorolac as a subacromial injection along with lidocaine. Each patient was evaluated in terms of visual analog scale (VAS) for evaluating pain and Constant's score for function evaluation (pain, activity level, and range of motion with standard goniometry). The patients were re-examined 1 and 3 months after intervention. All the patients educated for simple home exercise. Findings: At 1 and 3 months of follow-up, both treatment arms resulted in an increased range of motion and decreased pain. The difference between the groups was not statistically significant (P > 0.05). In ketorolac group, mean pre- and post-treatment (at 12 weeks) VAS scores were 8.6 (range, 3-9) and 4.5 (range 2-4), respectively. In steroid group, mean pre- and post-treatment (at 12 weeks) VAS scores were 8.3 (range, 3-10) and 3.9 (range, 0-7), respectively. The difference was statistically significant within groups at baseline and 1 (P < 0.001) and 3 (P < 0.001) months after the injection. Conclusion: Subacromial injection of ketorolac has an equivalent outcome to subacromial injection of corticosteroid. The use of ketorolac injections can substantially decrease the pain and increase the range of motion of the shoulder and could be a reasonable alternative in case of corticosteroid contraindications.